Thought Stoping dalam Menghadapi Ansietas Klien Hipertensi - Aprida Manurung (Jurnal Anestesi, 2024)
Background: Hypertension is an increase in blood pressure that exceeds normal limits (120/80 mmHg). Hypertension can be caused by lifestyle, diet and genetics (heredity), apart from that, factors that can trigger an increase in blood pressure levels are psychological factors, namely anxiety, which if not treated will result in depression so that the client is reluctant to treat hypertension until the client experiences a stroke and death . In theory, one therapy that nurses can do to prevent this is by providing Thought Stopping relaxation therapy. Objective: It is hoped that Thought Stopping therapy can reduce respondents' anxiety. Research design: This research used a case study research method on 5 respondents conducted for 3 days on responses that had just been identified as hypertension (last 1-3 months). Before and after the research, respondents were asked to fill out the Self-Reporting Questionnaire (SRQ)-20). Research results: After implementation, there was a decrease in scores for respondents 1 to 3 from a score of 8 to 4, respondent 4 from a score of 9 to 4 and respondent 5 from a score of 10 to 5. Conclusion: With this research it can be concluded that Therapy Thought Stopping can reduce anxiety. Suggestion: This therapy is highly recommended in reducing anxiety in clients who have just been diagnosed with hypertension so that clients are willing to carry out consistent care/treatment.